La teoría de Vygostky y el pensamiento crítico en los docentes del Instituto Superior Pedagógico de Huancavelica - Manrique Chávez, Zoraida Rocío (2018)
In teacher education, one of the basic skills that the teacher should have to meet the roles assigned to it is knowing how to learn, as I could not teach "learning to learn " if it does not have this ability. In this context, the teacher is required to circulate within a paradigm of conceptualization, application, analysis, synthesis and evaluation of information from observation, experience, reflection, reasoning, or communication that allows deal appropriately within their social and cultural context. Lev S. Vygotsky argues that psychological processes are changing and depend largely on the living environment. Therefore, the development of individuals can only be explained in terms of social interaction. Critical thinking is to analyze and evaluate the structure and consistency of reasoning, particularly opinions or assertions that the teacher accepts as true in the context of socio-cultural life. In this sense, this research began with the purpose of determining the level of critical thinking that is manifested in teachers Public Pedagogical Institute of Huancavelica in relation to the characteristics of Vygotsky's theory. To achieve this objective, a descriptive study with 8 teachers from the institution, with a design only after a group, to which they applied two instruments: a survey of self- observation and record videos made ​​based didactic sessions to the standards and strategies proposed intra and interpsychological Vygotsky 's theory. The results obtained from the analysis of the data obtained show that all teachers have a critical thinking level above acceptable. In addition, we obtained a Pearson correlation coefficient of  the results in terms of both instruments, validated by studens t test with a significance level of 0.05 and a coefficient of proportionality of shared or explained variability 53%. This research highlights and allows us to reflect that in teaching practice, teachers should radically change their relationship with the knowledge that will need to be active, critical and should perceive themselves and act not only as creators and transmitters knowledge.